Assessing genetic variability in Cycas dolichophylla (Cycadaceae) - Tâm Nguyễn Minh; Trang Nguyễn Thị Phương; Hiệp Nguyễn Tiến; Lý Trần Đình; Triest, Ludwig (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 79-88, 2005